Prospects of Developing Islamic Financial Institutions in North Bolaang Mongondow Regency, Indonesia - Sabihi, Fidyah Handayani; Suleman, Tantri (Department of Sharia Financial Management, Institut Agama Islam Negeri Sultan Amai Gorontalo, Indonesia, 2022)
The objective of this research is to look into the future of Islamic financial institutions in North Bolaang Mongondow Regency, North Sulwesi Province, Indonesia. The research methods employed are qualitative in nature. The analysis is used to reduce the data, present the findings, generate conclusions, and validate them. The availability of human resources, opportunities, and the engagement of local governments all influence the development possibilities of Islamic finance. Human Resources (HR) are a consideration in North Bolaang Mongondow Regency. Human resources are an essential component of any company or institution. North Bolaang Mongondow Regency, is one among the regions with the potential to build Islamic Financial Institutions, given the following considerations: The population is predominantly Muslim, with strong government support for foreign investors. The government provides possibilities for any investor who wishes to create and build a business in North Bolaang Mongondow, and the local government is also willing to promote the development of the Islamic Financial Institution business.